Bamboozle as a Learning Media to Improve Extragenesis-Based Speaking Skills - Mulyana, Ajeng Tina; Fajarsari, Dwi Desi; Dourahu, Masrin (LPPM Universitas Mohammad Husni Thamrin, 2025)
Speaking skills are essential abilities acquired through experience, social interaction, and education, thus falling under extragenetic knowledge transmitted through culture rather than genetics. Speaking skills serve not only as a means of conveying information, but also as a medium for expressing ideas, building social relationships, and constructing and negotiating meaning in the communication process. In an educational context, speaking skills are an indicator of learning success because they reflect students' ability to understand, process, and communicate the knowledge they have acquired effectively. This study aims to analyze how the interactive quiz platform Bamboozle can be utilized to enhance learners’ speaking skills based on the principles of extragenesis. The method employed is a literature review, examining books and scholarly articles related to extragenesis, speaking skills, and gamification/interactive quizzes, sourced from Scopus-indexed journals and other relevant publications. The findings indicate that speaking skills can be developed through active practice in interactive learning contexts, and Bamboozle provides a platform for learners to practice responding, engaging in discussion, and receiving instant feedback, thereby improving retention and motivation. Based on these results, it is recommended that educators integrate Bamboozle as a learning tool to support speaking skill development, combining game elements and interactivity to maximize extragenetic knowledge transfer, and encourage broader application in both online and face-to-face learning to continuously enhance students’ communication abilities.